Judicial control of the reasoning of arbitration awards: Analysis of case law and proposal - Velásquez Meléndez, Raffo (2025)
In this paper, the author conducts a critical analysis of the practice adopted by the Commercial Chambers of Lima, which have been requiring arbitral awards to contain reasoning comparable to that of judicial decisions, relying on an extensive and debatable interpretation of Article 61.1.b of the Arbitration Law, despite the fact that both jurisdictions respond to inherently different natures.To this end, the author conducts a rigorous study of the doctrinal sources, the main national and foreign scholarly contributions, as well as the case law of the Commercial Chambers and the Constitutional Court, together with the applicable legislative framework. In particular, the study addresses the absence of an express ground for annulment of arbitral awards based on defects in reasoning, and advances an interpretative alternative to address this issue without resorting to questionable normative extensions.